Literasi Digital pada Perempuan Pelaku Usaha Produktif di Daerah Istimewa Yogyakarta - Dhyah Ayu Retno Widyastuti; Ranggabumi Nuswantoro; Thomas Adi Purnomo Sidhi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2016)
This research aims at identifying the reality of women activities in using digital media. This research was conducted at Usaha Mikro Kecil dan Menengah (UMKM) in Daerah Istimewa Yogyakarta. Using qualitative research approach to observe information among informants, this resaerch found that women have limited access to information and communication technology. Women used digital media to get information to support their activities. They used mobile phone and personal computer to access the internet. The use of mobile phone was more than personal computer. Based on the result, this research recommends that digital literacy played important role to sustain women activities. The process of adoption of innovative technologies enhances women capability to improve UMKM activities. In addition, internet access enhances women’s economic sustainability.